MANAJEMEN PEMASARAN BISNIS SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DESA CIARUTEUN ILIR, KECAMATAN CIBUNGBULANG, BOGOR - Tubagus Rifqy Thantawi; Miftakhul Anwar; Nur Khopifah (SAHID DEVELOPMENT JOURNAL, 2022)
This Community Service has a background that there are still many violations of ethics and Islamicvalues from business behavior that should have Islamic ethics, especially in marketing activitiesor consumer search. Good and professional sharia marketing management is needed. It is hopedthat MSME business actors in Ciaruteun Ilir Village, Cibungbulang District, Bogor have highcompetitiveness and ever-increasing profits.